Measuring the success of canine and feline preventative healthcare consultations: a systematic review - Robinson, N.J.; Belshaw, Z.; Brennan, M.L.; Dean, R.S. (Elsevier, 2018)
Preventative healthcare consultations account for a large proportion of the veterinary caseload. This novel study is the first to methodically review all literature on canine and feline preventative healthcare consultations. Previous research has found these consultations to be different from health problem consultations in terms of communication style and content. Identifying relevant evidence and previously validated methods of measuring the success of these consultations will be useful when implementing strategies for optimisation. The aim of this study was to identify and assess the quality of existing literature which describes and/or measures the success of preventative healthcare consultations.